Pelatihan Paralegal Pos Bantuan Hukum Desa atau Kelurahan Bersama Kementerian Hukum di Wilayah Sumatera Utara - Azmiati Azmiati (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
Legal aid services play a crucial role in ensuring access to justice for the community, particularly for vulnerable groups and underprivileged communities in villages and sub-districts. However, limited legal knowledge and the lack of legal assistance in rural areas often lead to various legal issues being unresolved effectively. This community service activity was carried out with the aim of improving the capacity of village/sub-district officials and the community through paralegal training at Legal Aid Posts (Posbakum) in North Sumatra. The activity method was carried out using a participatory approach through legal counseling, paralegal skills training, simple case handling simulations, and interactive discussions. The results showed that the training was able to improve participants' understanding of basic legal knowledge, mediation techniques, out-of-court dispute resolution, and procedures for providing legal aid to underprivileged communities. In addition, this activity also helped increase public legal awareness and strengthen the existence of village/sub-district Posbakum as a community-based legal service medium. Therefore, paralegal training is one of the strategic efforts to expand access to justice in North Sumatra.